Time spent in different types of childcare and children's development at school entry: an Australian longitudinal study - Gialamas, A; Mittinty, M; Lynch, J; Zubrick, SR; Sawyer, MG; Sawyer, M; Zubrick, S; Mittinty, MN (My University, 2014)
Objective: To investigate whether the total amount of time in childcare through the first 3 years of life was associated with children’s receptive vocabulary, externalising and internalising problem behaviours at age 4-5 years, and whether this association varied for different types of childcare. Methods: We used data from the prospective, population-based Longitudinal Study of Australian Children (n=3208–4066, depending on outcome). Parental reports of the time spent in different types of child care were collected at face-to-face interviews at age 0-1 years and at age 2-3 years. Children’s receptive vocabulary was directly assessed in the child’s home, and externalising and internalising behaviours were measured by questionnaire, completed by parents and teachers at age 4-5 years. Results: At 3 years of age, 75% of the sample spent regular time in the care of someone other than the parent. After adjustment, more time in childcare was not associated with children’s receptive vocabulary ability but was associated with higher levels of parent-reported (β=0.10 (95% CI 0.00 to 0.21)) and teacher-reported (β=0.31 (0.19 to 0.44)) externalising problem behaviours and lower levels of parent-reported internalising problem behaviours (β= -0.08 (-0.15 to -0.00)). Compared with children who did not attend any type of childcare, children in centre-based care had higher parent-reported and teacher-reported externalising and lower internalising problem behaviours. Conclusions: More time in centre-based child care (but not other types of care) through the first 3 years of life was associated with higher parent-reported and teacher-reported externalising problem behaviours, and lower parent-reported internalising problem behaviours but not with children’s receptive vocabulary ability at school entry.
Keywords: Child Care; Child Development -- Behaviour; Child Development -- Speech and Language; Childhood and child development; Child Care; Child Development; Behaviour; Speech and Language; Childhood and child development